Language of violence: Do words matter more than we think?. Issue 1 (26th October 2022) - Tatebe, Leah C; Thomas, Arielle; Regan, Sheila; Stone, Levon; Dicker, Rochelle
Abstract : Firearm violence is a leading cause of morbidity and mortality among young adults. Identification of intervention targets is crucial to developing and implementing effective prevention efforts. Hospital Violence Intervention Programs (HVIPs) have used a multiprong social care approach to mediate the cycle of interpersonal violence. One struggle continually encountered is how to change the conversation around the future. Speech patterns have been associated with health outcomes and overall behavior modification. During violence prevention efforts, young victims of violence say things such as 'I'm living on borrowed time' and 'why should I worry about getting an education when I'll likely die soon anyway?' Such speech patterns may contribute to the cycle of violence and increase the likelihood of reinjury. Presented is a narrative review of the impact language has on health outcomes and how psychotherapy may be able to change thought patterns, alter language structure, and ultimately reduce risk of reinjury. The biopsychosocial model of health posits that a person's health is dictated by a combination of biological, psychological, and social factors. By understanding that language exists in the personal context, it can serve as both an indicator and a tool for targeted interventions. Cognitive–behavioral therapy (CBT) works by retraining thought and speech patterns to affect change in emotion, physiology, and behavior. It is proposed here that CBT could be used in the HVIPs' multidisciplinary case management model by involving trained psychotherapists. Language is an important indicator of a patient's psychological state and approach to life-changing decisions. As such, language alteration through CBT could potentially be used as a novel method of injury prevention. This concept has not before been explored in this setting and may be an effective supplement to HVIPs' success.